Targeting NLRP3 and AIM2 signaling pathways by Viscosol alleviates metabolic dysregulations induced inflammatory responses in diabetic neuro- and nephropathy: An in silico and in vivo study - Summan Thahiem; Muhammad Ihsan; Hamza Muneer; Aamir Sohail; Mehmand Khan; Iram Murtaza; Zia Uddin; Muhammad Shafique; Khalid J. Alzahrani; Hamid Ali; Imran Ullah (PLoS ONE, 2025)
Type 2 Diabetes (T2D) is a chronic metabolic disorder, considered the fastest growing pandemic of the 21stcentury. Meta-inflammation is a pivotal characteristic of T2D. Hyperactivated PTP1B, NLRP3, and AIM2 inflammasomes are considered the major regulators of metabolic inflammation. The concept of diabetes as an inflammatory disease has changed the pathogenic vision of T2D and hence, the compounds that mitigateinflammation in the setting of T2D are under the limelight of research. Current study aimed to evaluatethe anti-inflammatory potency of Viscosol, a novel PTP1B inhibitor, isolated from Dodonaea viscosa, in the STZ-HFD-induced T2D mouse model. Herein, male mice(C57BL/6), were administrated with Streptozotocin (STZ) (40mg/kg) and Viscosol (33mg/kg), intraperitoneally. Computational profiling revealed good absorption, distribution, metabolism and excretion (ADME) properties, least toxicity, and high docking score of Viscosol with PTP1B(−6.4 kcal/mol), NLRP3(−7.2 kcal/mol), and AIM2(−7.4 kcal/mol). Viscosol treatment significantly restored normal body weight (p < 0.0001), decreased the blood glucose level (p < 0.001), serum ROS level(p < 0.05) and diminished the severity of histopathological lesions, inflammatory lobules and increased the cell count of both brain and kidney tissues. The RT-qPCR analysis showed that Viscosol significantly reduced the mRNA expression of PTP1B, NF-κB, NLRP3, and AIM2up to 2.7-folds, 2.6-folds, 5.7-folds and 14.2-folds in the kidney tissues and 1.6-folds, 1.2-folds, 10.2-folds and 1.5-folds in brain tissues. Conclusively, inhibition of PTP1B via Viscosol could attenuate meta-inflammation by suppressing the aberrant NLRP3 and AIM2 inflammasome signaling in diabetes-linked pathophysiology.